TRANSFORMASI TRADISI BASALE KE DALAM KESENIAN TARI DAN MUSIK DI SEKOLAH DASAR - Adelia Nur Thahira; Saputri, ⁠Anggraini; Putra, Ihsan Syah; Rahmawati, ⁠Nawang Anggi; Aisyah, Tiara; Ramadhani, ⁠Ulfa; Amalia, Vita; Agustin, Vivi Sahwitri; Putri, Yuliani Cindyana; Destrinelli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to transform the Basale tradition into dance and music as a medium for cultural arts education in elementary schools. The method used is a qualitative approach with a documentation study, analyzing documents such as historical records of Basale, articles, and previous research. The analysis of the Basale tradition identifies key elements, such as spiritual, social, and cultural values, to develop authentic and educational dance movements and musical compositions. The results show that the dance movements produced reflect the rituals and unique expressions of Basale, such as prayers to ancestors and collective movements symbolizing unity, while the musical composition maintains traditional rhythmic patterns to preserve its original cultural values. This transformation not only preserves the cultural heritage of the Anak Dalam Tribe but also enhances students' awareness of cultural identity and character values. This study supports previous findings that emphasize the importance of traditional arts in character education and cultural preservation. In conclusion, the transformation of the Basale tradition into dance and music contributes positively to cultural preservation and cultural arts education based on local values.